Welcoming delegates from the Faculty of Pharmacy, University of Santo Tomas / Zakiah Mohd Noordin - Mohd Noordin, Zakiah (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), had the distinct honour of hosting esteemed delegates from the Faculty of Pharmacy, University of Santo Tomas (UST), Philippines, on February 12, 2025. This visit marked a significant milestone in fostering international collaboration and strengthening ties between the two prestigious institutions.